PENGEMBANGAN KECAKAPAN SOSIAL SISWA DALAM PEMBELAJARAN IPS DI SEKOLAH DASAR - Syudirman; Juwita Umi Yarsih Rezeky (Walada: Journal of Primary Education, 2023)
This research was motivated by the fact that the school had several strategies used by teachers to develop students’ social skills. This aims to develop the social aspect because basically every student will need help from other people to become a social person, but in reality, there are still students who are unable to communicate with other people. This research aims to find out about teachers’ strategies, the obstacles faced by teachers, and how teachers overcome obstacles in developing student’s social skills in social studies subjects in class V at SDN 41 Ampenan.This research uses a descriptive qualitative approach. Data collection techniques were carried out in three ways, namely observations, interviews, and documentation. Meanwhile, data analysis uses data collection techniques, data reduction, data presentation, and conclusion drawing. Data validity testing uses four methods, namely credibility, transferability, dependability, and confirmability. Based on the research results, it was found that the teacher’s strategy in improving social skills in social studies subjects in class V. namely by getting students to work together in groups, teaching empathy, showing a participative attitude, and instilling discipline. As for the obstacles teachers face, namely students’ personalities, and the influence of peers and parent students. How to overcome obstacles in developing social skills student. How to overcome obstacles in developing social skills students, namely the solution of the student’s personality, the solution of peer influence and the solution is to establish cooperation between teachers and parents of students.